Penerapan Bimbingan Kelompok Dengan Teknik Self Management Untuk Mengurangi Kebiasaan Terlambat Siswa - Nurhidayatullah; Nur Halim AR (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
This study examines the application of self-management in group guidance to reduce late habits of students at SMA Negeri 12 Makassar. The purpose of this study was to determine: (1) An overview of the implementation of Self Management in group guidance at SMA Negeri 12 Makassar. (2) Description of students' late habits before and after being given self-management in group guidance at SMA Negeri 12 Makassar. (3) Self management in group guidance can reduce the habit of being late for students at SMA Negeri 12 Makassar. The approach used is quantitative experiment with Pre-Experiment design. The subjects of this study were 12 people who were class XI students who were taken from simple random sampling technique. Collecting data using questionnaires, observation and documentation. Data analysis used descriptive statistical analysis and non-paramentic analysis, namely the Wilcoxon test using SPSS 16.00. The results showed that: (1). Implementation of self management is divided into three parts, namely introduction, implementation and evaluation and termination. In the implementation section, it is divided into four stages, namely self-monitoring, self-control, stimulus control and self-punishment. From the research results, it can be concluded that students actively participate in self-management activities well. (2) The level of late habits of students at SMA Negeri 12 Makassar before treatment (pretest) is generally in the high category. However, after students were given self-management techniques, they showed a significant change from a high level of late habits to a low late habit. (3) The application of self-management techniques can reduce the late habit of students at SMA Negeri 12 Makassar